María Pilar González-Conde Puente, La guerra y la paz bajo Trajano y Adriano, Madrid, Fundación Pastor de Estudios Clásicos, D.L. 1991 ISBN 84-404-9012-7 (Minerva, 2019)
Review: María Pilar González-Conde Puente, La guerra y la paz bajo Trajano y Adriano, Madrid, Fundación Pastor de Estudios Clásicos, D.L. 1991 ISBN 84-404-9012-7